Abzug von Eigenkapitalzinsen als Betriebsausgaben: ein steuersystematischer Beitrag zur Krisenabsicherung von Unternehmen - Rose, Manfred; Zöller, Daniel (Perspektiven der Wirtschaftspolitik, 2012)
Abstract: The article deals with the development of a new model for taxing personal capital income and business profits incorporating elements of a (lifetime oriented) ACE system and of a traditional system of capital income taxation. This new approach adheres to decision neutrality at the enterprise level while taking into account both international competitiveness of company taxation and the requirement to meet the redistribution goal of the government. Neither a purely consumption based tax system nor the traditional tax system is capable to meet these requirements in a similar way. The distinctive core of the new system is that – according to the ideal approach of taxing lifetime income – notional interest on equity capital is deductible from the taxable profit of enterprises irrespective of their legal form. Interest income, dividends and capital gains received by individuals will be taxed according to a flat rate tax when they are withdrawn from their qualified bank accounts. Compared to the status quo, the introduction of the proposed tax system in Germany would make equity financing of investments more attractive. This could provide companies with the necessary cushion to survive financial or economic crises as they would be equipped with more equity capital.